Emotion Intelligence Based on Smart Sensing - Whang, Mincheol; Park, Sung (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue explores empirical studies of emotional mechanisms, qualitative and quantitative measurements of emotion, the recognition of emotional contexts, and the application of emotion. We introduce fourteen papers, ranging from lab-based studies aimed at understanding emotional mechanisms to applying emotion recognition in the real world (e.g., in driving, games, education, and virtual avatars). This Special Issue explores empirical studies of emotional mechanisms, qualitative and quantitative measurements of emotion, the recognition of emotional contexts, and the application of emotion. We introduce fourteen papers, ranging from lab-based studies aimed at understanding emotional mechanisms to applying emotion recognition in the real world (e.g., in driving, games, education, and virtual avatars).